Learners’ Subject-Verb Agreement and Simple Past Defect Analysis on Written Text in Learning English as a Foreign Language (EFL) - Eka Dian Rahmanu; Ni Made Kariati; Kumiko Shishido (Politeknik Negeri Bali, 2020)
General principles of linguistics would be related to structure and grammar that has two specific types, for instance subject – verb agreement and simple past which were analyzed and concerned by the researcher. Furthermore, this research focused on what kind of subject-verb agreement and simple past defect chosen by the students in written text. In line with that, the researcher chose 143 responders who study and learn English as a Foreign Language in business administration department in Polytechnic State of Bali and the results were collected by using internet assisted test. In gaining the results, the researcher found that the participants mostly tended to choose the wrong answer from 10 questions were given by the lecturer. Responders could not decide or choose plural or singular noun and surprisingly learners could not take valid simple past which were provided on the options as these determine the correct sentence based on the principle grammar rule.